Acute pleiotropic effects of dapagliflozin in type 2 diabetic patients with heart failure with reduced ejection fraction: a crossover trial. (11th August 2021) - Ilyas, Fahmida; Jones, Lynette; Tee, Su Ling; Horsfall, Matthew; Swan, Amy; Wollaston, Fiona; Hecker, Tracy; De Pasquale, Carla; Thomas, Simeoni; Chong, William; Stranks, Steve; Mangoni, Arduino A.; et al.
Abstract: Aims: This study aimed to explore the rapid effects of dapagliflozin in heart failure with reduced ejection fraction (HFrEF). Methods and results: We studied the functional, echocardiographic, electrophysiological, lung ultrasound, ambulatory blood pressure (BP), microvascular and macrovascular function, and biochemical effects of 2 week treatment with dapagliflozin in 19 type 2 diabetic HFrEF patients in a double‐blind, crossover, placebo‐controlled trial. Dapagliflozin had no significant effect on clinical, functional, or quality of life parameters. Dapagliflozin reduced systolic BP [114 (105, 131) vs. 106 (98, 113) mmHg, P < 0.01] and diastolic BP [71 (61, 78) vs. 62 (55, 70) mmHg, P < 0.01]. There was no effect on cardiac chamber size, ventricular systolic function, lung ultrasound, or arterial wave reflection. Dapagliflozin increased creatinine [117 (92, 129) vs. 122 (107, 135) μmol/L, P < 0.05] and haemoglobin [135 (118, 138) vs. 136 (123, 144) g/L, P < 0.05]. There was a reduction in ventricular ectopy [1.4 (0.1, 2.9) vs. 0.2 (0.1, 1.4) %, P < 0.05] and an increase in standard deviation of normal heart beat intervals [70 (58, 90) vs. 74 (62, 103), P < 0.05]. Unexpectedly, dapagliflozin increased high‐sensitivity troponin T [25 (19, 37) vs. 28 (20, 42) ng/L, P < 0.01] and reduced reactive hyperaemia index [1.29 (1.21, 1.56) vs. 1.40 (1.23, 1.84), P < 0.05]. Conclusions: After 2 weeks, while multiple parameters supported BP reduction and haemoconcentration with dapagliflozin, reduction in cardiac filling pressure, lung water, and functional improvement was not shown. Reduced ventricular ectopic burden suggests an early antiarrhythmic benefit. The small increase in troponin T and the reduction in the reactive hyperaemia index warrant further mechanistic exploration in this treatment of proven mortality benefit in HFrEF.